Pochwała człowieka poszukującego w monografii D. Kuboka pt. "Krytycyzm, sceptycyzm i zetetycyzm we wczesnej filozofii greckiej", Wydawnictwo Uniwersytetu Śląskiego, Katowice 2021. - Nerczuk , Zbigniew (Collectanea Philologica, 2024)
D. Kubok’s monograph entitled Krytycyzm, sceptycyzm i zetetycyzm we wczesnej filozofii greckiej (Criticism, Skepticism and Zeteticism in Early Greek Philosophy) addresses the issue of critical themes in early Greek thought. The work aims not to discuss skeptical antecedents but to find critical attitudes and motives in Greek literature (from Homer to the Sophists) using the author’s understanding and typology of criticism, skepticism and zeteticism.